PENGEMBANGAN MATERI AJAR SHOROF PADA KITAB AMTSILATU TASRIFIYAH DENGAN MENGGUNAKAN MEDIA CANVA BERBASIS INTERAKTIF - Puspita Sari, Dia; Wasilah, Wasilah; Irmansyah, Irmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop interactive Shorof learning materials based on the Amtsilatu Tasrifiyah textbook using Canva to enhance students’ motivation and understanding of tashrif patterns. The study was conducted at SMP IT Terpadu Robbani Palembang, where Shorof learning still relies heavily on conventional lecture and memorization methods, resulting in low student engagement and difficulties in understanding word patterns (wazan). This research employed a Research and Development (R&D) method using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate) with quantitative and qualitative approaches. Data were collected through classroom observations, teacher interviews, student questionnaires, and pre-test and post-test assessments. The results indicate that the development of Canva-based interactive Shorof materials effectively improved students’ learning outcomes and engagement. Students’ average scores increased from 62.47 in the pre-test to 81.53 in the post-test, with N-Gain categorized as medium–high, indicating significant improvement in understanding tashrif patterns. Student responses also showed high engagement (90.52%). The interactive features, including visual slides, animations, audio, and navigation buttons, facilitated memorization, deepened understanding of wazan relationships, and reduced cognitive load from traditional memorization methods. Interactive and engaging learning experiences made Shorof learning more meaningful and enjoyable.